SOLID MEDICAL WASTE MANAGEMENT COSTS BETWEEN OUTSOURCING AND SELF-MANAGED SYSTEM AT HOSPITAL DURING THE COVID-19 PANDEMIC - Billy Zia Napoleon Bayusunuputro; Chriswardani Suryawati; Nurjazuli Nurjazuli (Poltekkes Kemenkes Semarang, 2021)
Health service programs aim to improve the level of society’s health. On one side, it will give benefit public health, and on the other side, it will have a bad impact if the process is not managed appropriately. Health service activities produces wastes, one of which is solid waste. It is important to know the problem related to the process and cost of the solid medical waste management, which is part of the B3 wastes (hazardous and toxic wastes). The B3 waste management is under the supervision of public health facilities which have the security and cost responsibilities. The costs include investment cost, maintenance cost, cooperation cost or cost of the third-hand management, and consumable cost. This study compares solid medical waste cost between outsourcing systems and self-management systems in the X hospital during the Covid-19 pandemic. This study uses descriptive research in a qualitative approach through observation, document review, and cost calculation for data collection. The study results show that the process of solid medical waste management has been running well. In addition, self-managed solid medical waste management is cheaper than outsourcing management.